2020
DOI: 10.1108/ijphm-07-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Factors that motivate young people’s intention to undergo cosmetic surgery in Vietnam

Abstract: Purpose The purpose of this study is to assess the factors that motivate young people’s intention to undergo cosmetic surgery in Vietnam. Design/methodology/approach This study applies Ajzen’s theory of planned behavior as a research model. The study is based on a quantitative method that applied exploratory factor analysis. Findings In total, 412 valid responses are used for the statistical analysis. The results confirm that subjective norm (SN), attitude toward cosmetic surgery and perceived behavioral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In addition, the results of the inequality analysis show a significant difference between these two groups. The results of this study are similar to the results of Hormozi et al 9 , Alharethy 29 , Schlessinger et al 30 , Nguyen et al 27 ; while the study by Frederick et al 32 is not in line with our findings, depicting that young and single women were less likely to use CSS than married women. Apparently, single people are looking to choose a spouse, so they have elicited a greater tendency to use CSS in order to have more and better choices.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the results of the inequality analysis show a significant difference between these two groups. The results of this study are similar to the results of Hormozi et al 9 , Alharethy 29 , Schlessinger et al 30 , Nguyen et al 27 ; while the study by Frederick et al 32 is not in line with our findings, depicting that young and single women were less likely to use CSS than married women. Apparently, single people are looking to choose a spouse, so they have elicited a greater tendency to use CSS in order to have more and better choices.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the present study showed that the highest number of cosmetic surgeries were performed in a female-headed household; this is because the female caregiver being the ultimate decision maker in the family, has a naturally higher tendency to encourage the use of these services. Various studies led by Hormouzi et al 9 , Salihahmadi 12 , Alharethy 29 , Schlessinger et al 30 , Wu et al 24 , Nguyen et al 27 , and Jovic et al 31 confirm that cosmetic surgeries were higher among females than males. The dominance of female attractiveness may explain their naturally higher tendency for cosmetic surgeries.…”
Section: Discussionmentioning
confidence: 94%
“…Tuy nhiên, xu hướng tiếp thị thông qua các phương tiện thông tin đại chúng và người nổi tiếng đã có tác động lớn đến nhận thức cá nhân [3]. Với sự chấp nhận ngày càng nhiều của việc chỉnh sửa sắc đẹp, số lượng bác sĩ và cơ sở phẫu thuật thẩm mỹ đa dạng, cũng như các kỹ thuật phẫu thuật an toàn hơn, ngày càng có nhiều người châu Á quyết định thực hiện các loại phẫu thuật thẩm mỹ [10,11]. Phẫu thuật thẩm mỹ ở châu Á Thái Bình Dương dự kiến sẽ tăng trưởng đáng kể và đạt tốc độ tăng trưởng kép hàng năm cao nhất là 5,96% trong vòng 8 năm tới (từ 2020 đến 2028) [12] .…”
Section: đặT Vấn đềunclassified
“…Việt Nam là một quốc gia đang phát triển với dân số trẻ và nhu cầu làm đẹp ngày càng tăng [11]. Theo ghi nhận từ một báo cáo quốc gia, Việt Nam có hơn 20 bệnh viện và 320 phòng khám phẫu thuật thẩm mỹ tư nhân bên cạnh hàng ngàn cơ sở chăm sóc sắc đẹp.…”
Section: đặT Vấn đềunclassified
“…Hầu hết các trường hợp được phẫu thuật thẩm mỹ là những người cảm thấy không hài lòng với ngoại hình của mình [14]. Theo Nguyễn Quốc Cường, tại Việt Nam, ba yếu tố thúc đẩy người trẻ phẫu thuật thẩm mỹ là thái độ, nhận thức và hành vi [15]. Làn sóng văn hóa Hàn Quốc xâm nhập vào Việt Nam cũng đang làm gia tăng số lượng người phẫu thuật thẩm mỹ, bệnh nhân muốn có vẻ đẹp giống như thần tượng và có thể thuận tiện hơn trong cuộc sống [16].…”
Section: đặT Vấn đềunclassified